A Training for Strengthening Character Education Through Traditional Games Based on The Socratic Method for Teachers in Elementary School - Lutfi Nur; Nandang Rusmana; Mesa Rahmi Stephani; Dodi Suryana; Rangga Gelar Guntara; Krisna Sujaya; Rosarina Giyartini; Elis Solihati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The educational process in the new normal era presents challenges for teachers in order to accelerate the increase in learning activities for students and achieve comprehensive and optimal education based on needs, as well as student development. One of the main focuses at the elementary school level is strengthening character education. The purpose of this article is to conduct training on the application of strengthening character education through traditional games based on the Socratic Method for teachers in elementary schools in Tasikmalaya. The implementer of this community service program were lecturers of UPI Tasikmalaya Campus. The method of implementing the service was carried out through several stages, namely Focus Group Discussion (FGD), seminars/training, workshops, and mentoring as well as supervision and evaluation. The research was located in Tasikmalaya, while the target was teachers in elementary schools. The results of this activity were obtained by the teachers regarding the strengthening of theory and practice (planning, implementation, evaluation) of traditional games that were integrated with the Socratic Method in an effort to develop character values in students. The teachers responded well to this learning innovation as a form of increasing their competence. The implication of this activity is that teachers are expected to be able to apply their knowledge to students in their respective schools.